Decoding glycosylation in cardiovascular diseases: mechanisms, biomarkers, and therapeutic opportunities - Li, Gang; Ren, Kaidi; Jin, Yage; Yang, Yang; Luan, Yi (Frontiers in Pharmacology, 2025)
Protein glycosylation, particularly O-GlcNAcylation, is a critical post-translational modification (PTM) that regulates cardiac and vascular functions by modulating protein stability, localization, and interactions. Dysregulated glycosylation is generally believed as a key driver in the pathogenesis of cardiovascular diseases (CVDs), contributing to adverse cardiac remodeling, mitochondrial dysfunction, metabolic dysregulation, and vascular inflammation. This review highlights the mechanistic roles of glycosylation in CVD progression, including its regulation of cardiac remodeling, mitochondrial dysfunction, and vascular inflammation. This study explored the dual role of O-GlcNAcylation in acute protection and chronic injury, emphasizing its potential as a biomarker for early diagnosis and risk stratification. Therapeutic strategies targeting glycosylation pathways, particularly O-GlcNAc transferase (OGT), and O-GlcNAcase (OGA), hold promise for addressing myocardial ischemia-reperfusion injury, diabetic cardiomyopathy, and atherosclerosis. Advances in glycosylation profiling and interdisciplinary collaboration are essential to overcome challenges such as tissue specificity and off-target effects, advancing precision cardiovascular medicine.